Geology of the region between Darica-Asagiulupinar villages and origin of the Kepezdagi volcanics, Malatya, Turkey - Beyarslan, Melahat; Kali, Bulent (Geological Soc India, 2006)
The Kepezdagi volcanics of Middle-Upper Miocene age occur between Kozluca and Balaban in the western part of Malatya (in the Eastern Taurus Orogenic Belt). These unconformably overlie Yenice and Balaban Formations of Eocene age and constitute one of the youngest volcanics of the Eastern and Southeast Anatolian Regions. These units are composed of basalt and andesite lava flows and pyroclastic rocks. The petrographic and geochemical data presented in this paper indicates that the Kepezdagi volcanics are formed from magmas derived in the mantle. These magmas are effected by subduction enrichment, assimilation and contamination during their ascent through the crust.
Keywords: Kepezdagi volcanics; geochemistry; petrography; Malatya; Turkey